Tree planting and smart tagging project for a Malay enclave in IIUM - Abdullah, Fadzidah; Sanusi, Aliyah Nur Zafirah; Azmin, Aida Kesuma; Yusof, Zeenat Begam; Mohd Din, Azreen; Ibrahim, Mohd Sharifuddin; Salleh, Elias; Kassim, Mohd Hisyamuddin (2019)
Malaysia’s Sustainable Development Goals (SDG) calls for sustainability that runs in manifold directions, including in the aspects of natural, cultural and social sustainability. This project intends to cover some spectrum of sustainability by re-planting trees for natural preservation, instilling awareness among youth on the importance of nature for sustaining cultural lifestyle and having collaborative academic action for social sustainable incorporation. In addition, Malaysia has also formulated the National Framework on Industrial Revolution 4.0 (IR 4.0). Hence, this project will be integrated with the usage of SMART Tag, that has informative description of trees in the form of videos, stored in cloud. The target group for this sustainable project are the students of Kulliyyah of Architecture and Environmental Design (KAED), International Islamic University Malaysia (IIUM). It is crucial to engage the young generation on sustainable project as they are the group who undertaken the Industrial Revolution IR 4.0 and will be the future leaders. Hopefully they could integrate IR 4.0 with sustainable initiative that has minimum negative impact on human and the “blue planet”. They are also the group who will be responsible to pass the notion of sustainability to the successive generation. IIUM Malay Enclave is chosen as the site for tree-planting project because of the nature of its establishment that promotes preservation and conservation of architectural heritage. The Malay Enclave is a project of re-constructing and re-locating a 110 years old Rumah Kutai Perak, at a site in IIUM. This small initiative is significant in sustaining the natural environment, instilling nature-care concept as cultural lifestyle among the youth and encouraging the youth to socially work together to hold the inspiration of sustainability. This project is also relevant to the United Nation’s Sustainable Development Goal (SDG) that calls for the halt of biodiversity loss (SDG 15). In a nutshell, this project is appropriate to Selangor Strategic Plan (Pelan Strategik PSUK Selangor,2018-2022).